Korean economic dynamism - Das, Dilip K. (London, 1992)
The Korean economy has experienced astoundingly rapid growth during the period 1960-90 and is now able, despite its late start, to compete with mature indust rialised economies. This book focuses on the underlying economic factors behind this unprecedented growth performance, exam ining the failures as well as the undoubted successes of such a development process.
Keywords: South Korea